2006
DOI: 10.1177/039463200601900407
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofBifidobacteriuminfantison Interferon- γ- Induced Keratinocyte Apoptosis: A Potential Therapeutic Approach to Skin Immune Abnormalities

Abstract: Current management of atopic dermatitis is mainly directed to the reduction of cutaneous inflammation. Since patients with atopic dermatitis show abnormalities in immunoregulation, a therapy aimed to adjust their immune function could represent an alternative approach, particularly in the severe form of the disease. Indeed, T-lymphocytes constitute a large population of cellular infiltrate in atopic/allergic inflammation and a dysregulated T-cell induced keratinocyte apoptosis appears to be an important pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…For example, Bifidobaterium infantis prevents skin disorders-associated immune abnormalities, while Lactobaillus reuteri protects epidermal keratinocytes from staphylococcus. Further, other LAB can act as probiotics by alleviating infantile eczema [30][31][32].…”
Section: Beneficial Effects Of Probiotics For Maintaining Good Skin Cmentioning
confidence: 99%
“…For example, Bifidobaterium infantis prevents skin disorders-associated immune abnormalities, while Lactobaillus reuteri protects epidermal keratinocytes from staphylococcus. Further, other LAB can act as probiotics by alleviating infantile eczema [30][31][32].…”
Section: Beneficial Effects Of Probiotics For Maintaining Good Skin Cmentioning
confidence: 99%
“…It has been reported that different probiotic strains, including the VSL3# preparation, increase epithelial barrier function by stabilizing tight junctions and inducing mucin secretion in epithelial cells [57, 58]. Furthermore, several probiotic bacterial strains are able to protect the epithelium, presumably by the aforementioned mechanisms, from various insults, including pathogenic bacteria [59, 60] and inflammatory cytokines [61, 62]. More recently, Rizzello et al showed that fermentation with a complex formula of sourdough lactobacilli decreased the concentration of gluten to below 10 ppm [63].…”
Section: Enzyme Therapymentioning
confidence: 99%
“…In contrast, a recent study reported that specific proteins secreted by probiotic Lactobacillus rhamnosus GG (LGG) suppress apoptosis of TNF-a-activated IECs (46). Another study documented that extracts of the probiotic Bifidobacterium infantis suppressed T-lymphocyte-induced apoptosis of human keratinocytes in an atopic dermatitis model (47), and probiotics suppressed Citrobacter rodentium-induced apoptosis following colonic infection in mice (48). Perhaps probiotics have different effects on antigen-presenting cells (APCs) and epithelial cells, or different probiotic strains either promote or suppress apoptosis of specific cell types.…”
Section: Probiotics and Innate Immunity: Cytokines And Apoptosismentioning
confidence: 99%